Evaluating stage-wise irrigation water requirement of sweet orange (Citrus sinensis) c.v. Sathgudi grown on Alfisols (Current Horticulture, 2024)
A field experiment on stage-wise water requirement was conducted on pan evaporation replenishment through drip irrigation system in a 10- year- old bearing sweet orange (Citrus sinensis Osbeck) cv. Sathgudi at AICRP Fruits(Citrus), Citrus Research Station, Dr YSR Horticultural University, Tirupati, Andhra Pradesh, during 2012- 2017. The treatments comprised : irrigation schedule with 30% ER in stage-I, III, V and 40% ER in stages II, IV and VI (T1), irrigation schedule with 40% ER in stage-I, III, V and 60% ER in stages II, IV and VI (T2), irrigation schedule with 60% ER in stage-I, III, V and 80% ER in stages II, IV and VI (T3), irrigation schedule with 80% ER in stage I to VI (T4) and irrigation schedule with 30% ER in stage I to VI (T5) with four replications in a randomized block design. The maximum canopy volume (20m3), average number of fruits of fruits (288 fruits/plant) and total soluble solids (10.63°Brix) were recorded at 80-80-80-80-80-80% ER from stage I (January-February) to stage VI (November-December). However, maximum fruit yield (46.91 kg/plant and 13 t/ha), less incidence of dry root rot (8.33%) and highest benefit:cost ratio (1.48) were recorded at 60-80-60-80-60-80% ER in stages I to VI. The reduction in irrigation from 80% ER to 30% ER during any stage resulted in consequent reduction in yield from 13.00 to 10.19 t/ha. Hence, it is recommended that irrigation at 60-80-60-80-60-80% ER from stages I (January February) to VI (November-December) for better plant growth, fruit yield and quality with efficient utilization of water, besides water saving of 13% per plant and highest benefit with and also low incidence of dry root rot disease (8.33%) for Ambia bahar crop of sweet orange under Rayalaseem region of Andhra Pradesh.
Keywords: Stage wise; Drip irrigation; Water requirement; Alfisols; Irrigation schedule